PROSES COLLABORATIVE GOVERNANCE DALAM PENGELOLAAN DANA DESA - La Ode Islamy; Rininta Andriani (Politeknik STIA LAN Makassar, 2022)
The authority of the village government in managing the Village Fund in principle is the right of the village government which is adjusted to the priority needs of the community based on the principle of justice. The village government is given full authority every year to set priorities for the use of village funds for the development and empowerment of village communities. Therefore, collaboration is an absolute thing for village government do considering all limited resources and capabilities and networks they have to support the implementation of programs or policies. The purpose of this research is to illustrate the collaborative governance process in managing village funds that focuses on Face to Face Dialogue, Trust Building, Commitment to Processes, Shared Understanding, and Intermediate Outcomes. The method used is qualitative with the support of data analysis techniques, including data collection, data reduction, and data presentation, as well as conclusion drawing. The significance of this research is expected to be able to contribute to the development of collaboration theory in village government management while, practically it is expected to contribute ideas, especially regarding the management of village funds carried out by collaborative governance. The results of the study show that the established dialogue, both formally and informally, builds mutual trust with each other so as to generate benefits for the community. This is based on a commitment to share understanding and knowledge about village fund management.